STUDYING THE DROUGHT-RESISTANCE OF BERRY PLANTS - Mavlyanovich, Abdullaev Ravshan; Ravshanovna, Abdullaeva Khilola; Abdukodirovich, Kosimov Akhmadjon (International Journal of Psychosocial Rehabilitation, 2020)
The article presents the data about drought-resistance of berry fruits cultivars, such as strawberry and golden currant, and also studies the water amount and water deficiency on the leaves of strawberry and golden currant cultivars which belong to different ecological groups. Having taken the samples of the leaves of strawberry and golden currant before irrigation and after irrigation in experimental fields of investigation, the air temperature, its relative humidity, the influence of water amount and soil moisture on water deficiency have been studied too.